Functional Capacity Improvement on Patent Ductus Arteriosus with Pulmonary Arterial Hypertension: A Case Report and Literature Review - Annis Rakhmawati; Irsad Andi Arso; Anggoro Budi Hartopo; Lucia Kris Dinarti (ACI (Acta Cardiologia Indonesiana), 2019)
Pulmonary artery hypertension (PAH) is a pathophysiological disorder involving a wide range of clinical conditions. This can be a condition of complications from heart disease and respiratory system. Pulmonary arterial hypertension is defined as an increase in mean pulmonary arterial pressure (mPAP) ≥ 25 mmHg at rest assessed by right heart catheterization. The cardiovascular rehabilitation program is a set of efforts to improve the underlying cause of cardiovascular disease such that it can maintain or restore the best conditions and secondary prevention. Cardiac rehabilitation and physical exercise programs have the benefit of improving pulmonary vascular endothelial function, physical activity capacity and quality of life parameters for PAH patients. A 6-minute walk test can be used to assess the functional capacity of PAH patients.